Further Properties of β-Pascu Convex Functions of Order α - H. Özlem Güney; Grigore Stefan Sâlâgean (International Journal of Mathematics and Mathematical Sciences)
We obtain several further properties of β-Pascu convex functions of order α which were recently introduced and studied by Ali et al. in (2006).